2021
DOI: 10.1007/s11187-021-00481-w
|View full text |Cite
|
Sign up to set email alerts
|

Does patenting always help new firm survival? Understanding heterogeneity among exit routes

Abstract: While patents are a valuable resource ensuring the competitive advantage of firms, there is limited evidence on the role of patents in the survival and exit strategies of new firms. To fill the gap in the literature, we examine whether the effects of patenting on new firm survival vary according to exit routes (bankruptcy, merger, and voluntary liquidation), while considering the endogeneity of patenting. We use a large-scale sample of new firms in the Japanese manufacturing and information services sectors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 131 publications
(243 reference statements)
2
12
0
1
Order By: Relevance
“…In general, the average loan that ends in default does so between 22 and 25 months after its origination. This is consistent with a large body of empirical evidence on loan default (Cowling et al, 2021;Glennon and Nigro, 2005), and more general firm survival after start-up (Holmes et al, 2010;Kato et al, 2022).…”
Section: Data and Descriptive Statisticssupporting
confidence: 87%
“…In general, the average loan that ends in default does so between 22 and 25 months after its origination. This is consistent with a large body of empirical evidence on loan default (Cowling et al, 2021;Glennon and Nigro, 2005), and more general firm survival after start-up (Holmes et al, 2010;Kato et al, 2022).…”
Section: Data and Descriptive Statisticssupporting
confidence: 87%
“…For startups and small firms the role of patents is still questioned. For example, the size of the patent portfolio does not necessarily improve sales performance among small firms (Agostini et al , 2015), while it does seem to decrease the likelihood of bankruptcy (Kato et al , 2021). Several studies have found that small firms have lower patent propensities than large firms (Arundel and Kabla, 1998; Brouwer and Kleinknecht, 1999; Chirico et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Intangible capital, including intellectual property, data, design, trademarks and organisational capital, plays a decisive role in increasingly knowledge-based economies. Recent research on Japan suggests that patenting reduces bankruptcy risk and increases the odds of exit via merger and voluntary liquidation (Kato et al, 2021). In the case of liquidation, a rapid reallocation of transferable intangibles, such as intellectual property and data, supports the diffusion of technology and productivity growth.…”
Section: Box 7 Intangible Assets and Insolvency Regimesmentioning
confidence: 99%